Design Validation of Hub Stream Pump Impeller using Computational Fluid Dynamics - Narisi Reddy, Tamanampudi; Kumar M., Vijay (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The Technology used in Pumps is a proved, applications and usage are universal. Hub stream pump is a machine designed to convert mechanical vitality into fluid energy by rotational motion of an impeller. The axial flow pump (Low Head and High Flow) is chosen because it is widely used in Power Transformers for cooling Purpose (Recirculation oil in closed loop). The reason for this paper is to compute the plan computation of hub stream pump impeller which can deliver Fluid vitality by lifting activity of the pump impeller blades. In this paper, the flow rate and head of hub stream flow pump are 0.0 3m3/sec and 2.5 Mts. The rotation speed is 1500 rpm. The paper, especially involves the design calculation of propeller type impeller running in a Suction casing of the pump. The result data of impeller are outlet diameter is 152 mm, the hub diameter is 98.8mm. The number of blades is five. The clearance between impeller and pipe or casing is 0.152mm. The designed hub stream flow pump satisfies the requirements of Power Transformer.